Shinto festival involvement and sense of self in contemporary Japan - Roemer, Michael K. (Japan forum, 2010)
In recent decades, hundreds of studies have addressed connections between religious beliefs and behaviours and individual well-being in Europe and the US. There are only a handful of publications that examine these important links in Japan, however. In this paper, I rely on participant observation and in-depth interviews with some of the leaders of Kyoto's Gion Festival to illustrate associations between public ritual involvement and sense of self. Specifically, this paper is a sociological exploration of relationships between annual participation in the Gion Festival and self-esteem. In Japan, as in other cultures, self-esteem is an important component of well-being, and this study reveals that the men who are heavily involved in the rites, parades and other events of the Gion Festival have a positive sense of individual and collective self-worth. (Jpn Forum/GIGA)